PENERAPAN COMPUTER ASSISTED INSTRUCTION (CAI) DALAM PEMBELAJARAN PENGUCAPAN KOSAKATA BAHASA NIAS BERBASIS WEB - BUGIS, ERMINSYAH (Majalah Ilmiah Kaputama, 2019)
Computers as part of the development of technology have been used in various aspects including advocating, implementing educational evaluation processes as part of a culture of the means to transmit values and ideas where everyone is able to play a role in transforming values for the progress of the nation and state. One technology that is developing quite rapidly in the world of education is Web technology that is utilized for learning applications. Many Nias people do not understand Nias language, especially in terms of pronunciation of the Nias language vocabulary that does have its own uniqueness. The Nias language recognizes 22 alphabets, which are 6 vowels A, E, I, O, U and are added with Ö (read as "e" weak). As the word "Saohagõlõ" means thank you, use the vowel "Ö" (Halawa N., 2014), and 16 consonantal letters B, D, F, G, H, K, L, M, N, R, S, T, W, ?, Y, Z, but in some areas there are changes in the mention of letters by not changing the writing. One of the most widely used Web-based learning media is applications that are packaged in the form of computer software called Computer Aided / Assisted Instruction (CAI). Computer Aided / Assisted Instruction applications strongly support more interesting and effective learning. Because this application is designed as a source of learning for the process of teaching and learning with computer assistance where students face and interact directly with computers. The choice of Nias language is due to the uniqueness and difficulty in translating Nias language so that it makes it easy for users who want to learn Nias language.